The Rocky Road towards Professional Autonomy: The Estonian Journalists’ Organization in the Political Turmoil of the 20th Century - Lauk, Epp (2017)
This article attempts to explain the relationships between journalists, politics and the state from the perspective of collective autonomy, that of the professional organization of journalists. The case of Estonian Journalists’ Union demonstrates the complexity and historical contingency of professional autonomy of journalism. The development of the Estonian journalists’ organization occurred as a sequence of transformations from the Estonian Journalists’ Association to the Estonian Journalists’ Union to the Soviet type journalists’ union, and lastly to an independent trade union. This sequence was disrupted by several fatal breakdowns that changed not only the character of the association, but also professional values, the whole occupational ideology and the conditions of the existence of journalism as a profession in Estonia.